Long term outcome in unilaterally treated retinopathy of prematurity: a case report. - Mushawiahti M; Rokiah O; Umi KMN; Leow, SN (Penerbit UKM, 2014)
Retinopathy of prematurity (ROP) is a disorder describing an immature vascularisation of a developing retina in low birth weight preterm infants. This condition potentially leads to blindness. ROP developed as a response of hypoxia of the eye due to incomplete development of the retinal vessels. ROP is commonly reported as bilateral disease,a small percentage of infants have asymmetrical changes. We report a case of long-term outcome of a asymmetry ROP changes with peripheral retinal ablation in a single eye. This particular case demonstrates the possible long-term outcome of unilaterally treated ROP which could either be due to the severity of the disease itself or the treatment she received. It is important to highlight the possibility of unequal development of the eye in asymmetrical presentation of ROP.